MECHANISM OF ACTIVATION OF THE QUIESCENCE-SPECIFIC p20K GENE - Xie, Wenli (My University, 2014)
Growth arrest specific (GAS) genes are highly inducible at quiescence (G0) and repressed rapidly in response to mitogens. Aberrant disruption of quiescence can lead to abnormal development and diseases such as cancer, thus, it is important to study the signals and mechanisms responsible for expressions of quiescent specific genes. p20K, a GAS gene whose expression is highly induced in conditions of contact inhibition & hypoxia in chicken embryo fibroblasts (CEF), is studied in this thesis. Preliminary studies demonstrate that p20K activation is dependent on its Quiescence Responsive Unit (QRU), a 48bp promoter region. In addition, the binding sites of a CCAAT/enhancer binding protein (C/EBPβ) and ERK2 on the QRU of p20K promoter overlap with each other regulating the competition between activating (C/EBPβ) and inhibiting (ERK2) of the p20K gene. After culturing CEF with media rich in growth factors (10%FBS), p20K induction is delayed in hypoxia. Moreover, it is the decrease of Phospho-ERK not CHOP level that correlates with p20K inhibition in hypoxia in both 5%CCS and 10%FBS. Western blotting analysis of Hypoxia Inducible Factor 1α (HIF1α) expression indicated that this hypoxia-response factor is induced rapidly and with the same kinetics in CEF subjected to hypoxia cultured in 5%CCS or 10%FBS, indicating that they sense and respond similarly to low oxygen concentrations. These results suggest that p20K induction in hypoxia is caused by growth arrest induced by hypoxia. To further document this process, hypoxia mimicking reagent DMOG, a prolyl-hydroxylase inhibitor that can stabilize HIF in normoxia, was used. Interestingly, p20K expression was highly induced after DMOG treatment in CEF, even if CHOP, an inhibitor of C/EBPβ, was induced in these conditions. Co-Immunoprecipitation results showed that the accumulation of CHOP-C/EBPβ heterodimers was induced during DMOG treatment. Additionally, Proliferation Assay suggested that DMOG treatment significantly inhibited CEF proliferation. Finally, Chromatin Immunoprecipitation Analysis indicated that ERK-2 did not bind to the QRU after DMOG treatment, indicating that ERK-2 dissociation correlates with p20K induction in response to DMOG in CEF. Collectively, these results demonstrate that growth arrest induced by hypoxia or DMOG treatment plays a determinant role in p20K induction. In contrast, CHOP level or CHOP-C/EBPβ heterodimer reduction did not correlate with the induction of p20K.
Keywords: quiescence-specific p20K gene activation